CHARACTERIZATION OF HEMOLYTIC ACTIVITY OF STAPHYLOCOCCUS AUREUS ISOLATED FROM PARANGIPETTAI COAST SOUTHEAST COAST OF INDIA - T. KATHIRAVAN; A. SUNDARAMANICKAM (International Journal of Pharma and Bio Sciences, 2013)
The rising development of pollution has been extensive to the marine environment, although it has been one of natural places more stable for years, it is polluted marine aquaculture worldwide at present is being severely affected. It will be linked inter-relationships between human health and the oceans. The opportunistic pathogen is Staphylococci 21 strains isolated from parangipettai coastal waters. Further Identification of S.aureus was confirmed as Biochemical tests and PCR by using universal primers 27F and1492R. These strains were analyzed for the detection of α, β and δ hemolysin on sheep, bovine and horse blood used hemolytic activity. Out of 21 strains there is only one strain can detect β-hemolytic activity and hemolysins producing strain were confirmed S.aureus.